Prevención del consumo de alcohol en mujeres de 16 a 35 años parroquiales Chical - Chamba Zurita, Viviana Marcela (2025)
Alcohol consumption in Ecuador is considered a social and public health problem given its serious consequences. In this context, the research focused on the prevention of alcoholism in women aged 16 to 35 years, in the Chical Parish, with the objective of implementing strategies to prevent alcohol consumption in this population. The methodology used was quantitative approach, using methods such as systemic analysis, which allowed us to conduct a comprehensive analysis of the problem, and the inductive-deductive method, as well. Besides, relevant bibliographic sources and descriptive field research were also used. The AUDIT Test was used as an instrument, thus obtaining significant results. 40% of the surveyed women reported consuming 10 or more drinks in a single day, while 44% stated that they were unable to stop drinking once they started, repeating this behavior weekly. 59% indicated that alcohol consumption was part of their daily routines, and 51% reported that they were unable to fulfill their responsibilities weekly due to this habit. Furthermore, 53% reported episodes of memory loss and 40% acknowledged them to have suffered or sustained injuries because of drinking. 60% of the surveyed women claimed not to have received family, social or professional support. Based on these findings, strategies were designed to address this issue, along with comprehensive and participatory interventions, promoting in this way, not only awareness but also skills development